The Crystal Structure of Nα-p-tosyl-lysyl Chloromethylketone-Bound Oligopeptidase B from Serratia Proteamaculans Revealed a New Type of Inhibitor Binding - Vladimir I. Timofeev (MDPI AG, 2021)
A covalent serine protease inhibitor—Na-p-Tosyl-Lysyl Chloromethylketone (TCK) is a modified lysine residue tosylated at the N-terminus and chloromethylated at the C-terminus, one molecule of which is capable of forming two covalent bonds with both Ser and His catalytic residues, was co-crystallized with modified oligopeptidase B (OpB) from Serratia proteomaculans (PSPmod). The kinetics study, which preceded crystallization, shows that the stoichiometry of TCK-dependent inhibition of PSPmod was 1:2 (protein:inhibitor). The crystal structure of the PSPmod-TCK complex, solved at a resolution of 2.3 Å, confirmed a new type of inhibitor binding. Two TCK molecules were bound to one enzyme molecule: one with the catalytic Ser, the other with the catalytic His. Due to this mode of binding, the intermediate state of PSPmod and the disturbed conformation of the catalytic triad were preserved in the PSPmod-TCK complex. Nevertheless, the analysis of the amino acid surroundings of the inhibitor molecule bound to the catalytic Ser and its comparison with that of antipain-bound OpB from Trypanosoma brucei provided an insight in the structure of the PSPmod substrate-binding pocket. Supposedly, the new type of binding is typical for the interaction of chloromethylketone derivatives with two-domain OpBs. In the open conformational state that these enzymes are assumed in solution, the disordered configuration of the catalytic triad prevents simultaneous interaction of one inhibitor molecule with two catalytic residues.